COMBINATIONS OF CYTOKINE AND MATRIX METALLOPROTEINASE GENES ASSOCIATED WITH RETINOPATHY IN TYPE 2 DIABETIC WOMEN - V. I. Konenkov; V. V. Klimontov; A. V. Shevchenko; V. F. Prokof’ev; O. N. Fazullina (Офтальмохирургия, 2015)
Purpose. To study the association of single nucleotide polymorphism (SNP) combinations of cytokine genes (IL1B, IL4, IL6, IL10, TNFA, VEGF) and matrix metalloproteinase genes (MMP2, MMP3, MMP9) with diabetic retinopathy (DR) in patients with type 2 diabetes (T2D).Material and methods. There were examined 103 Caucasoid females with T2D aged 50 to 70 years, including 49 with and 54 without DR. There were studied 13 SNPs in the promoter regions of following genes: VEGF: А2578С and С936Т; IL1В: С31Т; IL4: С590Т; IL6: G174C; IL10: A592C and А1082G; TNFА: А238G, A308G and A863C; MMP2: T1306C; ММР3: 5A/6A; MMP9: С1562T. Genotyping was performed by the method of restriction fragment length polymorphism.Results. There were revealed 37 SNP combinations positively associated with DR and 11 negatively associated combinations. DR-associated combinations included homozygous variants of VEGF (936CC), TNFA (308GG and 238GG), IL1B (31TT), IL4 (590CC), IL10 (592CC) and MMP9 (1592CC). In combinations negatively associated with DR there were heterozygous genotypes of TNFA (308GA) and IL10 (1082AG), and homozygous genotypes of IL1B (31CC), MMP2 (1306CC) and MMP3 (6A/6A).Conclusions. The variants of these genes may determine a susceptibility/resistance to DR, influencing the intensity of inflammation and angiogenesis in the retina.